2016
DOI: 10.18632/oncotarget.10613
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of MYH9 expression on patients with acute myeloid leukemia

Abstract: MYH9 expression has previously been demonstrated as an independent predictor of clinical outcome in solid tumors. However, the prognostic relevance of MYH9 expression in acute myeloid leukemia is still unclear. Here, we found high MYH9 expressers were seen more frequently in females and more frequently in M4 morphology. We also found high MYH9 expressers had lower percentage of bone marrow blasts. In addition, overexpression of MYH9 was associated with an inferior overall survival. Notably, distinct microRNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Moreover, down-regulating the MYH9 expression inhibited angiogenesis, migration, and invasion of esophageal cancer cells. Consistent with our research results, it was reported that expression of MYH9 is closely related to the malignant degree of cancer, and can be regarded as a marker for evaluating lymph node metastasis and poor prognosis in breast cancer [16], epithelial ovarian cancer [17] and acute myeloid leukemia [18]. Combined detection of vasculogenic mimicry, MYH9 and E-cad may play an essential role in predicting the invasion, metastasis, and progression of patients with ESCC [8,9].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, down-regulating the MYH9 expression inhibited angiogenesis, migration, and invasion of esophageal cancer cells. Consistent with our research results, it was reported that expression of MYH9 is closely related to the malignant degree of cancer, and can be regarded as a marker for evaluating lymph node metastasis and poor prognosis in breast cancer [16], epithelial ovarian cancer [17] and acute myeloid leukemia [18]. Combined detection of vasculogenic mimicry, MYH9 and E-cad may play an essential role in predicting the invasion, metastasis, and progression of patients with ESCC [8,9].…”
Section: Discussionsupporting
confidence: 88%
“…Among the proteins associated with FNDC3B, MYH9 had the highest interaction score and was selected for further analysis (data not shown). MYH9 has been reported to function as an oncogene in most types of cancer, and it plays an important role in tumor cell adhesion, migration, and proliferation 18‐20 . The exogenous and endogenous coimmunoprecipitation showed that FNDC3B could physically interact with MYH9 (Figure 4B), which was verified by the immunofluorescence staining that FNDC3B was colocalized with MYH9 in the cytoplasm of both SUNE‐1 and HNE‐1 cells (Figure 4C).…”
Section: Resultsmentioning
confidence: 68%
“…As a skeleton protein, MYH9 plays an important role in cell adhesion, polarity, migration, and proliferation through mediating the actin‐based contractile motion 32 . MYH9 is recognized as an oncogene, as it is closely related to the progress and poor prognosis of most solid tumors 18‐20 . For example, MYH9 overexpression was induced by LIM kinase 1 (LIMK1) and promoted growth and metastasis by activating MAPK/AKT signaling in colorectal cancer 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers conducted PCR experiments without the knowledge of clinical outcome. The methods for RNA extraction, complementary DNA synthesis and quantitative PCR were reported previously ( Yu et al, 2017 ). The commonly used housekeeping (HK) genes like β-actin , α-tubulin , GUSB and GAPDH were measured.…”
Section: Methodsmentioning
confidence: 99%
“…For the miRNA measurement, total RNA was obtained using a miRNeasy Mini Kit (Cat # 217004,QIAGEN, GmbH, Germany) following the manufacturer's instructions and subsequently checked for a RNA integrity number (RIN) to inspect RNA integration by an Agilent Bioanalyzer 2100 (Agilent technologies, Santa Clara, CA, US). The detailed methods for the miRNA experiments were described previously ( Yu et al, 2017 ). We deposited the raw and processed data at the National Center for Biotechnology Information Gene Expression Omnibus (repository number GSE103431).…”
Section: Methodsmentioning
confidence: 99%